The Importance of a Food Systems Approach to Low and Middle Income Countries and Emerging Economies: A Review of Theories and Its Relevance for Disease Control and Malnutrition - Alarcon, Pablo; Dominguez-Salas, Paula; Fèvre, Eric M.; Rushton, Jonathan (Frontiers in Sustainable Food Systems, 2021)
Our review explores the changing food production, distribution and consumption environment in low- and middle-income countries and emerging economies as a basis for framing how to study food systems in order to address public health issues of food safety and nutrition. It presents the state of knowledge on existing food systems science and its use in terms of sustainable actions for food safety and public health. The review identifies a knowledge gap on food system mapping and governance, with value chain mapping of key commodities often missing. Despite a number of initiatives, the application of food systems methods is highly variable in scope and quality. Most analyses concentrate on specific commodities, rarely taking into account the need for a whole diet approach when looking at nutrition or the assessment of a range of infectious agents and their interactions when looking at food safety. Of the studies included in the review there is a growing observation of ‘informal’ food systems, a term used inconsistently and one that requires revision. ‘Informal’ food systems link to the formal sector to provide food security, yet with trade-offs between economic efficiencies and food safety. Efforts to improve food safety are hampered by inadequate food safety capacities and a lack of policy coherence leading to: inadequate investment; fragmented food quality control systems; weak or non-existent traceability mechanisms; weak foodborne disease surveillance; obsolete food regulation; and weak regulatory enforcement. In-depth food systems assessments can complement risk analysis to identify risky behaviours and understand institutional settings in order to improve codes of practice and enforcement. Methods for looking at food safety from a food systems perspective are emerging, yet existing nutrition and food systems science are not advancing sufficiently in response to nutritional public health problems. There is an urgency for improved understanding of the structure and drivers of the food systems, for better planning of changes that leads to nutrients access and healthy levels of eating. It is proposed that countries and international institutions provide an atlas of food system maps for the key commodities based on an agree common methodology and developed by multidisciplinary teams.